Real-time stereo matching failure prediction and resolution using orthogonal stereo setups - Meier, Lorenz; Honegger, Dominik; Vilhjalmsson, Vilhjalmur; Pollefeys, Marc (2017 International Conference on Robotics and Automation (ICRA), 2017)
Estimating the depth from two images with a baseline has a well-known regular problem: When a line is parallel to the epipolar geometry it is not possible to estimate the depth from pixels on this line. Moreover, the classic measure for the certainty of the depth estimate fails as well: The matching score between the template and any pixel on the epipolar line is perfect. This results for common scenes in incorrect matches with very high confidence, some even resistant to left-right image checks. It is straightforward to try to address this by adding a second stereo head in a perpendicular direction. However, it is nontrivial to identify the failure and fuse the two depth maps in a real-time system. A simple weighted average will alleviate the problem but still result in a very large error in the depth map. Our contributions are: 1) We derive a model to predict the failure of stereo by leveraging the matching scores and 2) we propose a combined cost function to fuse two depth maps from orthogonal stereo heads using the failure prediction, matching score and consistency. We show the resulting system in real-time operation on a low-latency system in indoor, urban and natural environments.